If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -5) + 5x = 0 Reorder the terms: 5(-5 + x) + 5x = 0 (-5 * 5 + x * 5) + 5x = 0 (-25 + 5x) + 5x = 0 Combine like terms: 5x + 5x = 10x -25 + 10x = 0 Solving -25 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 10x = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 10x = 0 + 25 10x = 0 + 25 Combine like terms: 0 + 25 = 25 10x = 25 Divide each side by '10'. x = 2.5 Simplifying x = 2.5
| 4j-j=9 | | 10x+2(x-7)+4(2x-3)=134 | | 4.6=r-3.3 | | 150y=-110x+144000 | | 8x^3+2x^2-30x=0 | | 3x+64=139 | | 15y+4(3-2y)=0 | | 8=6+q | | 4.7x-18.35=2.8 | | 7r-5r=8 | | Z^2-225= | | 6p-3p=6 | | -5b-5y+10b-1+4b= | | -8x+3=-12+8xfraction | | 15u-11u=16 | | 7s+2=4(8+1) | | (3x-10)+y=180 | | 18m-17m=16 | | 3x(x-5)=2x+10 | | c=2x+2 | | p+23=2 | | 17.5+4x=-6.5*(3x-6) | | 17p+3p=20 | | -8x+3=-12+8x | | 3x+5.4=2x+1 | | Sqrt(4+7x)=sqrt(7x-9) | | 8+7x+2x+10z-5x= | | f-24=-12 | | 9(m+43)=729 | | -5(p+4)=-(p-8) | | 4+2x=3x+-1 | | 32*33= |